2020
DOI: 10.3390/ijms21155549
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Reveals Changes in Long Noncoding RNAs in the Differentiation of Canine BMSCs into Insulin-Producing Cells

Abstract: Long noncoding RNAs (lncRNAs) have been extensively explored over the past decade, including mice and humans. However, their impact on the transdifferentiation of canine bone marrow mesenchymal stem cells (cBMSCs) into insulin-producing cells (IPCs) is largely unknown. In this study, we used a three-step induction procedure to induce cBMSCs into IPCs, and samples (two biological replicates each) were obtained after each step; the samples consisted of “BMSCs” (B), “stage 1” (S1), “stage 2” (S2), “stage 3” (S3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The identified 4th passage canine BMSCs frozen in the laboratory ( 13 , 14 ) were amplified for 2 passages using complete α-MEM (α-MEM culture medium containing 10% fetal bovine serum, 1% 100 × Penicillin Streptomycin Solution and 0.25% Anti-Myc Mycoplasma scavenging reagent) in 60 mm petri dishes. The 6th passage BMSCs were prepared into 3 × 10 5 /mL cell suspensions, and 500 μL of the cell suspensions were inoculated (uniform drop cloth) on the drilling meniscus ( n = 3) and the control meniscus ( n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…The identified 4th passage canine BMSCs frozen in the laboratory ( 13 , 14 ) were amplified for 2 passages using complete α-MEM (α-MEM culture medium containing 10% fetal bovine serum, 1% 100 × Penicillin Streptomycin Solution and 0.25% Anti-Myc Mycoplasma scavenging reagent) in 60 mm petri dishes. The 6th passage BMSCs were prepared into 3 × 10 5 /mL cell suspensions, and 500 μL of the cell suspensions were inoculated (uniform drop cloth) on the drilling meniscus ( n = 3) and the control meniscus ( n = 3).…”
Section: Methodsmentioning
confidence: 99%
“…The GAPDH gene was used as an internal control. The specific measured methods were carried out as previously described 22 . The verification was repeated three times for each gene of each sample, and the gene expression level was quantified using the 2 −ΔΔCt method 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, hypothetically, their direct involvement in the replacement of lost epithelial cells is also possible. According to some reports, the potential of MSCs is not limited to differentiation into cells of mesenchymal origin; under certain conditions, their transdifferentiation into ectodermal and endodermal derivatives such as precursors of epithelial cells of the salivary glands (Mona et al, 2020), hepatocytes (Hwang et al, 2012;Yu et al, 2012), and insulinproducing cells (Wang et al, 2020b) is shown. The ability of MSCs to differentiate into enterocytes in vitro under the influence of microRNA and growth factors (Ye et al, 2018) or upon co-cultivation with intestinal epithelial cells has been reported, and upon injection of fluorescently labeled bone marrow MSCs into the stomach of an experimental mouse, their differentiation into gastric epithelial cells was observed (Okumura et al, 2009).…”
Section: The Rationale For Using Mscs In Gastroenterologymentioning
confidence: 99%